THE SOCIETY’S PERCEPTION TOWARDS THE IMPLEMENTATION OF THE QUR'AN VERSES IN THE MODE OF TRANSPORTATION: A STUDY OF LIVING QUR’AN - Miftahhuddin - (INNOVATIO: Journal for Religious Innovations Studies, 2022)
This study aims to analyze the actions of the community in making the verses of the Qur'an as a reminder towards Allah SWT placed in the transportation mode section. The method used to answer this research problem is a qualitative research paradigm with an interpretative/hermeunetic approach. The data collection technique was carried out using content analysis which was then elaborated or completed with the results of observations, interviews, and documentation. Meanwhile, to analyze the validity of the data is done by a triangulation. Based on the approach used, the researcher found out the following important things: First, drivers or riders who put verses of the Qur'an in their vehicles are to increase their confidence in driving, to increase their business development, to remember more God the Almighty, to be calmer, to increase their pray, and to be always careful when driving. Second, the other purpose is to make it easy to find a blessed sustenance, to pray while they are on the road, and be safe on their trip. Third, meanwhile the response from religious leaders regarding the use of the verses of the Qur'an in transportation modes are positve when it is not degrading the Qur'an and there should be a compatibility with vehicle users – they place the verses on the top front of the vehicle. Constrastly, there are negative views such as being stepped on or not respecting them. In addition, the verses of the Qur'an should not actually need to be placed in the transportation mode because if the drivers or riders really wish to read the Al-Qur'an, they can stop and implement at the prayer room or mosque. Abstrak: Penelitian ini bertujuan untuk menganalisis tindakan masyarakat dalam menjadikan ayat-ayat Al-Qur’an sebagai pusat ingatan menuju Allah Swt yang diletakkan pada bagian moda transportasi. Metode yang digunakan untuk menjawab permasalahan penelitian ini adalah paradigma penelitian kualitatif dengan pendekatan interpretative/hermeunetik. Teknik pengumpulan data dilakukan dengan menggunakan analisis isi (content analysis) yang kemudian dielaborasi atau dilengkapi dengan hasil observasi, wawancara, dan dokumentasi. Sedangkan untuk menganalisa keabsahan datanya dilakukan dengan trianggulasi. Adapun temuan dalam penelitian ini yaitu: Pertama, Pengguna kendaraan bertuliskan ayat-ayat Al-Qur’an mempunyai persepsi bahwa dengan adanya ayat tersebut semakin menambah keyakinan dalam berkendara, kelancaran dalam usaha, lebih ingat kepada yang maha kuasa, lebih tenang, selalu ingat untuk berdo’a, serta selalu berhati-hati dalam berkendara. Kedua, Tujuan dari penggunaan ayat-ayat Al-Qur’an di moda transportasi yaitu: agar mudah mencari rizki yang berkah, do’a dalam perjalanan, dan selamat dalam perjalanan. Ketiga, Adapun tanggapan dari tokoh agama terkait penggunaan ayat-ayat Al-Qur’an di moda transportasi yaitu: sesuatu yang positif ketika bersifat tidak merendahkan Al-Qur’an. Adanya kesesuaian dengan pengguna endaraan. Meletakkan ayat-ayat tersebut dibagian depan atas dari kendaraan. Namun ada negatifnya, seperti akan terinjak ataupun kurang menghormatinya. selain itu, seharusnya ayat-ayat Al-Qur’an itu juga sebenarnya tidak perlu diletakkan di moa transportasi. Karena jika menghendaki untuk membaca Al-Qur’an sebaiknya berhenti dahulu di musholla atau masjid. Kata kunci: persepsi, masyarakat, ayat-ayat al-qur’an, moda transportasi